Similarity Model Test of Coal Mining under Ordovician Limestone Nappe Aquifer. (17th March 2022) - Chu, Chengcheng
Abstract : Ordovician limestone in North China coalfield has the characteristics of karst fissure development and strong water yield. Coal mines in North China have been threatened by Ordovician limestone water for a long time. Taking the mining of 32 coal seam in the first eastern mining area of Qianyingzi coal mine in Anhui Province in China as the engineering geological prototype, this paper uses the self-developed fluid solid coupling similarity model test device to carry out the similarity model test of overburden stress and pore water pressure response of coal mining under Ordovician limestone nappe aquifer. Based on the variation law of pore water pressure and overburden stress in a stope, it can be seen that the variation law of pore water pressure in confined aquifer is jointly affected by two factors: the vertical distance between the monitoring point and coal seam and the horizontal distance between the monitoring point and DF200 fault. According to the analysis of experimental results, the maximum height of a water flowing fracture zone in the stope is fifteen times the mining thickness. Compared with the theoretical calculation results of empirical formula, the coupling effect of seepage field and stress field and the geological structure characteristics of the stope promote the development of a water flowing fracture zone. The research results of this paper have important theoretical and practical significance not only for the safe mining of Qianyingzi coal mine but also for the safe mining of the coal mine facing the double threat of roof Ordovician limestone confined aquifer and reverse fault.